Poetry as survival - Orr, Gregory (Life of poetry., 2002)
Intended for general readers and for students and scholars of poetry, Poetry as Survival is a complex and lucid analysis of the powerful role poetry can play in confronting, surviving, and transcending pain and suffering. Gregory Orr draws from a generous array of sources. He weaves discussions of work by Keats, Dickinson, and Whitman with quotes from three-thousand-year-old Egyptian poems, Inuit songs, and Japanese love poems to show that writing personal lyric has helped poets throughout history to process emotional and experiential turmoil, from individual stress to collective grief. More specifically, he considers how the acts of writing, reading, and listening to lyric bring ordering powers to the chaos that surrounds us. Moving into more contemporary work, Orr looks at the poetry of Sylvia Plath, Stanley Kunitz, and Theodore Roethke, poets who relied on their own work to get through painful psychological experiences. As a poet who has experienced considerable trauma--especially as a child--Orr refers to the damaging experiences of his past and to the role poetry played in his ability to recover and survive. His personal narrative makes all the more poignant and vivid Orr's claims for lyric poetry's power as a tool for healing. Poetry as Survival is a memorable and inspiring introduction to lyric poetry's capacity to help us find safety and comfort in a threatening world.